Analisis Persepsi Generasi Z Terhadap Sukuk, Saham Syariah, dan Reksadana Syariah Sebagai Pilihan Instrumen - Irawan Prabowo, Dicky (Jurnal Indonesia Sosial Sains, 2022)
The steps in investing are very necessary as initial reference material for potential investors and novice investors before they decide to invest. Over time, when technology and various economic development instruments synergize in accelerating development, in this millennial era, many industrial companies are targeting investors from the young community to be used as a source of company capital through the capital market. are activities in the capital market that do not conflict with sharia principles in the capital market and are part of the Indonesian capital market industry. Sharia principles in the capital market are based on the provisions of the Qur'an and Hadith which regulate worship and human activities in muamalah affairs which are then regulated in fiqh. Sharia shares are securities that represent equity participation in a company. Some things such as knowledge about investing in related sciences need to be deepened so that the investment activities we do are worth worship, get inner satisfaction and blessings in this world and the hereafter. Investment has two opposing sides, namely, return and risk. This type of research is qualitative with a literature study approach with data sources, namely secondary data obtained from previous studies, and other reference sources. There are several things that potential investors need to know. Especially investors from the millennial community related to investment planning and management in Islamic stocks. This requires investors to know the limits and rules of investment in Islam, both in terms of the process, purpose, object, and impact of the investment. The stock valuation is done through ratio analysis. The valuation ratio is a ratio that provides a measure of management's ability to create market value whose business is above investment costs